Rapid manufacturing of vacuum forming components utilising reconfigurable screw pin tooling - Wang, Zhijian (2010)
Current market trends are moving from large quantity production towards small batch production and mass customization. This has led to the high demand for the flexibility and adaptability of manufacturing technology and systems. Several reconfigurable pin type tooling systems have been proposed and developed to satisfy such demands. However, these reconfigurable tooling systems still suffer from several drawbacks, including difficulties associated with positioning and locking the pins and problems of uneven “staircase” surface effects from relying on discrete finite size pins.